PENGEMBANGAN APLIKASI SAKTI REMAJA SEBAGAI UPAYA OPTIMALISASI LAYANAN KESEHATAN JIWA UNTUK REMAJA - Nurhidayah, Reni; Bastian, Ardi; Kusuma Wati, Prima Dewi (Universitas Kadiri, 2024)
Abstract: Adolescents are particularly vulnerable to mental health issues due to significant physical, cognitive, emotional, and social changes, which can lead to stress, anxiety, depression, and destructive behavior. In Indonesia, adolescent mental health concerns are rising, with pesantren students showing elevated rates of mental health challenges, exacerbated by bullying and limited access to mental health services. This community service program developed and implemented the SAKTI-Remaja application, featuring self-screening, integrated mental health education, and counseling, tailored to the needs of pesantren students. The app was designed to support early detection and intervention by allowing self-assessment, delivering mental health education, and offering basic counseling resources. Three stages were implemented: app development, socialization of mental health awareness among pesantren administrators and students, and training for school health units (UKS) to maintain and utilize the app effectively. The results indicate that 85% of students found the app useful, while 95% of UKS members could apply the mental health screening feature proficiently. These findings demonstrate the SAKTI-Remaja application’s potential to improve mental health awareness and accessibility in pesantren, with implications for broader community-based mental health innovations.